(untitled) (Al-Qamar, 2021)
Islam, a complete code of life deals with every aspect of life and ensures success for its followers both in this world and in the hereafter. Islam gives balanced economic system and prohibits illegitimate ways of earning and usury/interest. Islamic economic system is discussed almost in 80 verses of the Holy Quran. Muslim jurists have streamlined the terms and conditions for Islamic Banking but annual reports of the banks show their failure in compliance with the Islamic rules which consequently decreases the trust of the people in Islamic banking but it doesn’t mean that this system has drawbacks but the mechanism for the practical implementation of the Islamic rules needs revision, supervision and monitoring in a strict manner. This paper appraises the contemporary Islamic Banking in the light of Seerah.